2020
DOI: 10.1111/joor.13087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multiple injections of botulinum toxin into painful masticatory muscles on bone density in the temporomandibular complex

Abstract: Background Adverse effects of masticatory muscle injections of Botulinum Toxin (Btx) have been noted in animal and, less dramatically, human studies. Objective Among women treated in multiple community‐based private practices, to compare TMJ bone density and mandibular condylar volume between patients with myofascial TMJD receiving multiple masticatory muscle Btx treatments and similarly diagnosed women not receiving such treatment. Methods Cohorts consisted of women whose treatment charts indicated a diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 47 publications
2
22
0
2
Order By: Relevance
“…In adult women with myofascial pain, a randomized clinical trial demonstrated a significant reduction of the volume of the mandibular condylar process at 3 months, after a high BoNTA dose injection in both the temporalis (25 U) and the masseter (75 U) muscles but not at lower doses (20 U and 50 U, respectively) ( 193 ). These results are consistent with a cohort study, which showed no bone loss at the mandibular condylar process in adult women with myofascial pain that underwent BoNTA interventions under 40 U in the masseter muscles when compared to match control population ( 194 ). These results support the hypothesis that masticatory muscle hypofunction negatively impacts mandibular bone homeostasis in humans, especially at the condylar process, when high doses of BoNTA are used.…”
Section: Muscle-bone Crosstalk At the Masticatory System In Health Ansupporting
confidence: 91%
“…In adult women with myofascial pain, a randomized clinical trial demonstrated a significant reduction of the volume of the mandibular condylar process at 3 months, after a high BoNTA dose injection in both the temporalis (25 U) and the masseter (75 U) muscles but not at lower doses (20 U and 50 U, respectively) ( 193 ). These results are consistent with a cohort study, which showed no bone loss at the mandibular condylar process in adult women with myofascial pain that underwent BoNTA interventions under 40 U in the masseter muscles when compared to match control population ( 194 ). These results support the hypothesis that masticatory muscle hypofunction negatively impacts mandibular bone homeostasis in humans, especially at the condylar process, when high doses of BoNTA are used.…”
Section: Muscle-bone Crosstalk At the Masticatory System In Health Ansupporting
confidence: 91%
“…Raphael et al 31 was a cohort study assessing bony change following at least two series of BoNTA injection into the masticatory muscles within the past year for ‘myofascial TMJD’. Of note, a portion of this group also received concurrent BoNTA injections for frequent migraine therapy into various muscles of the head, face and neck, as is standard protocol for chronic migraine 32 .…”
Section: Resultsmentioning
confidence: 99%
“…This effect is arguably to be expected, as menopause is concurrent with a decrease in oestrogen production, and oestrogen inhibits osteoclastic activity 42 . BoNTA dose appears to influence bony change, with higher doses leading to greater bone loss or decreased trabecular density 26,31 . Dose frequency also appears to influence bony change, as Lee et al showed that a second BoNTA injection series 4 months after the initial series led to greater bone loss than a single series 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is worth highlighting that application of low doses of BTX did not cause any bone-related damage and is a treatment recommended by the authors [ 52 ]. On the contrary, in 2020, Raphael et al, based on a cohort consisting of 35 patients, stated that multiple Botox injections failed to produce clinically significant bone changes [ 53 ]. Nevertheless, those studies indicate that multiple BTX treatments might be a cause of some significant adverse effects, and there is a need to monitor the patients undergoing BTX therapy, especially when high doses of the toxin are applied.…”
Section: Discussionmentioning
confidence: 99%